Technical characteristics of Macau Science Satellite-1A - Yan Li; Yong Zhang; TianYu Zhang; ShiGeng Yuan; Wen Su; JingShan Sun; Fei Feng; BingJun Cheng; Yi Jiang; PengFei Liu; GuiHong Xiao; QingMei Fan; et al. (Earth and Planetary Physics)
The Macau Science Satellite-1 (MSS-1) is the first space science satellite jointly developed on the Chinese mainland and in Macau. It comprises two satellites, named MSS-1A and MSS-1B, and holds considerable importance in China’s space exploration endeavors. Among these, MSS-1A is the world’s first high-precision scientific satellite dedicated to exploring the geomagnetic field and space environment at low latitudes. Equipped with two high-precision vector magnetometers and one scalar magnetometer, which are integrally installed on a highly stable nonmagnetic optical bench, the MSS-1A enables simultaneous high-precision measurements of both the Earth’s vector magnetic field and its scalar components. Its design integrates several state-of-the-art technologies, including arc-second-level thermal stability control, nonmagnetic thermal control for the optical bench, and ultra-high magnetic cleanliness control. These innovations effectively minimize magnetic interference originating from the satellite itself, thereby substantially improving the precision of geomagnetic field measurements and establishing a robust technical foundation for future magnetic survey satellite constellations.